THE DYNAMICS OF COPERATIVE FEDERALISMIN INDIA: CRITICAL ANALYSIS OF THE ROLE OF CENTRE IN COVIT 19 PANDEMIC - Dr.Om Krishna (Chelonian Research Foundation, 2023)
The pandemic COVID-19 is an unprecedented public health crisis that has prompted an unprecedented response. A key feature of India 's response to the COVID-19 outbreak has been the close collaboration and cooperation between the Union (central) and state governments .The study highlights the various steps taken by India's union government based on a strong vision of cooperative federalism, where a response is supported by the federal government, run by the state, and executed locally. A brief conclusion points out that the reliance on local and state actors in this pandemic was a pragmatic one, but also base on imperfect institutional choice, since initiatives at the state and local level are partial and porous by their very nature. They are necessarily hampered by the lack of uniformity and certainty that might arise from a federal pandemic response, and are unfortunately unfit to stop a novel virus in search of its next host. Keywords: COVID-19, uniformity, cooperative federalism, federally supported, imperfect institutional choice.